Uma análise sobre o mercado brasileiro de transporte aéreo - Giacomello, Rogério (2012)
This work aims to answer questions regarding the Brazilian aviation market, and how it behaves in terms of oligopolistic competition. That is, there are some firms in this sector competing for the same market, thereby analyzing issues among these firms, you may indicate issues of efficiency in this sector. Using data on market share of each company, and the elasticity of the aviation industry for the year 2009, it was mixed reviews on possible mergers in the airline market in Brazil, giving in each profile that elasticity which would potentially bring a greater distortion for the sector. The methodology for this was the model PCAIDS (Proportionality-Calibrated Almost Ideal Demand System), proposed by Epstein and Rubinfeld (2002) that simulates the merger of two companies in an oligopolistic market, and has an advantage of requiring fewer parameters to your pet than other methodologies. The findings suggest that the merger of GOL TAM will bring a higher price increases than other combinations that were made to give some scenarios that were tested.